Development of Canva-Based Interactive Student Worksheets Using the Problem-Based Learning Model - Nabila Syarifah; Moh. Affaf; Dwi Ivayana Sari (Journal of Practice Learning and Educational Development, 2025)
This study aims to develop interactive Canva-based Student Worksheets (LKPD) using the Problem Based Learning (PBL) model in grade IX of SMPN 3 Burneh. The background of this study stems from the need for innovative, interactive learning media that can increase student engagement and critical thinking skills in facing the challenges of the 21st century. This research is a development research using the 4D model (Define, Design, Develop, Disseminate). In the development stage, LKPD was designed based on an analysis of student needs, material concepts, and a contextual approach with the topic of statistics. Validation was carried out by material and media experts, as well as limited trials on grade IX students. The validation results showed that the developed LKPD had a high level of validity and practicality. The trial showed that this interactive LKPD could increase students' learning interest, active involvement, and critical thinking skills. Thus, the developed Canva-based interactive LKPD was declared suitable for use as a learning medium and can be an alternative in improving the quality of PBL-based learning in secondary schools.